Familia como espacio de resiliencia en las personas con capacidades diferentes de la Facultad de Ciencias Humanísticas y Sociales - Villamar Delgado, Mayra Ivonne (2020)
This research relates concepts of resilience and disability in a set of criteria that involves the family as the first social organization, therefore, it aims to identify the family as a space of resilience in people with different abilities from the faculty of humanistic sciences and social. For which a non-experimental type methodology was used, with an inductive-deductive approach, it was based on the descriptive, bibliographic method. The interview technique was used and as an instrument the interview guide and the Mexican RESIM resilience scale applied to a population and sample of 5 families of students of the faculty with families with disabilities. As a result, it is evident that the members of these families have a medium high and high standard in understanding resilience, this is related to the three elements analyzed, that is, the value that is given to resilience of a personal, family nature. and social allows them to look positively at the reality in which they live. To conclude The construction of resilience in the family that has people with different capacities, has a personal, family and community interrelation which leads to a point of intersection to strengthen this in a transversal way, that is, that use is made of the personal resources.